Antioxidant Activity of Bioactive and Mineral Constituents of Jatropha curcas Linn. (Euphorbiaceae) Leaf and Seed Extract - Shedrach Yakubu; Garbunga Yebpella (Journal of Chemical Natural Resources, 2024)
In recent years, there has been a surge in research on natural products, particularly plant-based ones, for pharmaceutical formulations and food supplements. Natural products rich in bioactive components like phenols, flavonoids, alkaloids, and saponins, and elemental minerals like Fe, Mg, Mn, and Cu, serve as antioxidants, anti-inflammatory, and antimicrobial agents. This study investigates the antioxidant capacity of Jatropha curcas leaves and seeds and the qualitative and quantitative phytochemical analysis and mineral compositions of the plant’s leaves and seeds. The samples were collected and treated before being extracted through cool maceration in methanol. The antioxidant activities of the methanol extracts were evaluated using the DPPH Assay after their concentration was achieved using a rotary evaporator. Both quantitative and qualitative analysis was conducted to investigate the presence of phytochemicals in both the seed and leaves of J. curcas. The presence of elemental minerals such as Fe, Mn, Cu, Zn, and Mg was investigated using AAS. The phytochemical analysis of J. curcas revealed the presence of phenols, flavonoids, tannins, saponins, and steroids in both leaves and seeds, while alkaloids and terpenoids were found in the leaves. The mineral composition indicates Mg levels of 1161.65 mg/Kg in leaves and 590.66 mg/kg in seeds, with Cu absent in leaves while Mn highest in leaves. The study found that Jatropha curcas leaves have the highest antioxidant activities (82.6%), competing with the ascorbic acid standard (86.2%), with less activity in seeds (52.7 %), suggesting the high potential of the leaves for pharmaceutical formulations and food supplements.